Sera from patients with Crohn’s disease break bacterial lipopolysaccharide tolerance of human intestinal epithelial cells via MD-2 activity - Seksik, Philippe; Sokol, Harry; Grondin, Virginie; Adrie, Christophe; Duboc, Henri; Pigneur, Benedicte; Thomas, Ginette; Beaugerie, Laurent; Trugnan, Germain; Masliah, Joelle; Bachelet, Maria (Innate immunity (London, England), 2010)
Myeloid differentiation (MD)-2 is linked to the cell surface as a Toll-like receptor (TLR) 4-bound protein though may also function as a soluble receptor to enable the lipopolysaccharide (LPS)-driven response. We recently demonstrated the importance of MD-2 either as a cell-associated or as a soluble receptor in the control of intestinal epithelial cell response toward LPS. High levels of circulating MD-2 were recently proposed as a risk factor for infectious/ inflammatory diseases as septic shock. We hypothesized that MD-2 might be present in sera from patients with inflammatory bowel disease and have pathogenic consequences. We analysed MD-2 activity in sera from patients with inflammatory bowel disease or from healthy subjects. We measured MD-2 activity as the capacity to mediate LPS-driven stimulation of intestinal epithelial cells (HT29). We found that sera from patients with inflammatory bowel disease, particularly Crohn’s disease, endowed HT29 cells with a markedly higher LPS-dependent stimulating capacity as compared to sera from healthy subjects. The effect of sera was specific for LPS activation and was reduced in the presence of anti-MD-2, and anti-TLR4 antibodies. We conclude that sera from patients with inflammatory bowel disease might contain increased MD-2. This might result in higher local availability of the protein leading to a loss of tolerance toward gut microbiota.